2020
DOI: 10.1002/solr.202000224
|View full text |Cite
|
Sign up to set email alerts
|

Stable Perovskite Solar Cells Enabled by Simultaneous Surface and Bulk Defects Passivation

Abstract: It is challenging to passivate defects that are buried in the depth of perovskite films; most of the reported passivation methods cannot reach the deep defects. Herein, methanol is adopted as a dual‐functional reagent to not only act as a solvent but also help the dissolved ions penetrate the depth of perovskite films. By treating the as‐prepared perovskite films with CsBr/methanol solution, Br− ions can react with the undercoordinated Pb2+, and Cs+ ions can fill in the cation vacancies. This strategy enables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Depositing high-quality perovskite films with few defects plays a crucial role in achieving efficient and stable perovskite solar cells (PSCs) [1][2][3][4][5][6][7] . Perovskite bulk doping and interface modification have been demonstrated to be effective in suppressing the bulk and interfacial defects [8][9][10][11][12][13] . It is reported that the perovskite formation process is sensitive to the surrounding atmosphere, like the solvent vapor, moisture, and others [14][15][16][17][18] .…”
mentioning
confidence: 99%
“…Depositing high-quality perovskite films with few defects plays a crucial role in achieving efficient and stable perovskite solar cells (PSCs) [1][2][3][4][5][6][7] . Perovskite bulk doping and interface modification have been demonstrated to be effective in suppressing the bulk and interfacial defects [8][9][10][11][12][13] . It is reported that the perovskite formation process is sensitive to the surrounding atmosphere, like the solvent vapor, moisture, and others [14][15][16][17][18] .…”
mentioning
confidence: 99%
“…A change in the tolerance factor can inevitably lead to a mismatch of the crystal lattice constant and explain the observed peak shifts in the XRD characterization . Therefore, the gradual shift of the characteristic peaks of the perovskite phase to higher diffraction angles can be attributed to the substitution of the vacant MA + and I – sites in the host perovskite by Cs + and Br – , which have smaller ionic radii, thereby decreasing the residual stress and decreasing the lattice constant . Thus, it is suggested that CsBr is integrated into the perovskite lattice.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the extra Cs + and Br − can bond with negatively‐charged defects (lead vacancy) and positively‐charged defects (halogen vacancy) through ionic bonds at the bottom of perovskite, reducing the non‐radiative recombination channel. [ 42 ] Additionally, the ions diffusion between the interface of CsBr and perovskite allows for Br − partially exchanging I − to form Br‐rich phase at the bottom of perovskite, appropriately expanding the bottom perovskite bandgap, achieving an ideal band bending and a better energy level alignment. [ 23,43–47 ]…”
Section: Resultsmentioning
confidence: 99%